Governance and trust in sustainability-based agri-food value chains. A comparative analysis of five cases in Germany - Grohmann, Pascal; Dietze, Victoria; Krämer, Christine; Feindt, Peter H. (Frontiers in Sustainable Food Systems, 2023)
Agri-food value chains that generate an increased willingness to pay among consumers by offering enhanced levels of sustainability are widely discussed as an important strategy for creating new business opportunities and fostering food system transformation. Previous research has highlighted the importance of governance arrangements to secure the trust necessary for the establishment of sustainability-based agri-food value chains. However, how different coordination designs by private and public actors along the value chain affect trust formation is not well understood. To address this question, this paper combines the concepts of hybrid governance and multidimensional trust to guide a comparative analysis of five sustainability-based agri-food value chains in Germany as exemplary case studies. The findings show that different types of governance activities are necessary to build the capacity to address four different sources of trust: dispositional, affinitive, rational and procedural trust. Building trust capacities facilitates coordination of activities along the value chain and reliable delivery of sustainability-related value propositions. In all five cases, governance arrangements and building of trust capacities were geared towards increasing willingness to pay. Sustainability-based agri-food value chains have therefore limited potential to internalize the agri-food sector’s substantial negative externalities.